“METHODS FOR ANALYZING SHIFTS IN ANIMAL HABITATS USING MODERN CARTOGRAPHIC TECHNOLOGIES” (Modern education and development, 2025)
The study of animal habitat shifts is critical for understanding ecological changes, biodiversity conservation, and climate change impacts. Modern cartographic technologies, including Geographic Information Systems (GIS), remote sensing, and species distribution modeling, have revolutionized habitat analysis. This article explores advanced methodologies for tracking and predicting habitat shifts, emphasizing the integration of satellite imagery, machine learning, and spatial statistics. Case studies demonstrate how these tools enhance accuracy in monitoring species migration, habitat fragmentation, and anthropogenic impacts. The findings highlight the importance of interdisciplinary approaches in wildlife conservation and sustainable land-use planning.